Adding acceptance and commitment therapy to exposure and response prevention for obsessive-compulsive disorder: A randomized controlled trial. (September 2018) - Twohig, Michael P.; Abramowitz, Jonathan S.; Smith, Brooke M.; Fabricant, Laura E.; Jacoby, Ryan J.; Morrison, Kate L.; Bluett, Ellen J.; Reuman, Lillian; Blakey, Shannon M.; Ledermann, Thomas
Abstract: The objective of this study was to test whether treatment acceptability, exposure engagement, and completion rates could be increased by integrating acceptance and commitment therapy (ACT) with traditional exposure and response prevention (ERP). 58 adults (68% female) diagnosed with obsessive-compulsive disorder (OCD; M age = 27, 80% white) engaged in a multisite randomized controlled trial of 16 individual twice-weekly sessions of either ERP or ACT + ERP. Assessors unaware of treatment condition administered assessments of OCD, depression, psychological flexibility, and obsessional beliefs at pretreatment, posttreatment, and six-month follow-up. Treatment acceptability, credibility/expectancy, and exposure engagement were also assessed. Exposure engagement was high in both conditions and there were no significant differences in exposure engagement, treatment acceptability, or dropout rates between ACT + ERP and ERP. OCD symptoms, depression, psychological inflexibility, and obsessional beliefs decreased significantly at posttreatment and were maintained at follow-up in both conditions. No between-group differences in outcome were observed using intent to treat and predicted data from multilevel modeling. ACT + ERP and ERP were both highly effective treatments for OCD, and no differences were found in outcomes, processes of change, acceptability, or exposure engagement. Highlights: Adding ACT to Exposure with Response Prevention (ERP) did not improve acceptability, engagement, or drop-out for OCD. ACT plus ERP and ERP alone both had high acceptability, engagement, and low drop-out. ACT plus ERP and ERP alone were both highly effective for OCD with no difference in outcomes.